2011
DOI: 10.3109/09638288.2011.610494
|View full text |Cite
|
Sign up to set email alerts
|

Chinese translation and validation of the Kujala scale for patients with patellofemoral pain

Abstract: The Chinese translated version of Kujala scale is a reliable and valid instrument for assessing the patellofemoral pain associated functional disturbances among the patient cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 15 publications
4
32
0
2
Order By: Relevance
“…Small to medium correlations (ranging from r= 0.13 to r =0.47) were found between all sub-scales of the SF-36 MHC and the Thai (Q1),26 Chinese (Q1)28 and Persian (Q2)35 versions of the Kujala Patellofemoral Scale. The SF-36 sub-scales of ‘social function’ and ‘mental health’ both demonstrated small correlations with the Functional Index questionnaire, r=0.23 and r=0.15, respectively (Q3) 34.…”
Section: Resultsmentioning
confidence: 90%
“…Small to medium correlations (ranging from r= 0.13 to r =0.47) were found between all sub-scales of the SF-36 MHC and the Thai (Q1),26 Chinese (Q1)28 and Persian (Q2)35 versions of the Kujala Patellofemoral Scale. The SF-36 sub-scales of ‘social function’ and ‘mental health’ both demonstrated small correlations with the Functional Index questionnaire, r=0.23 and r=0.15, respectively (Q3) 34.…”
Section: Resultsmentioning
confidence: 90%
“…Compared with the VAS score before muscle fatigue during step descent (r s Z À0.534, p Z 0.015), our results found a stronger association between the Kujala score and VAS score after muscle fatigue (r s Z À0.655, p Z 0.002). Kujala score is a very common clinical tool to measure the overall symptoms related to PFP in functional activities, including stair descent [21]. This result indicated that the immediate PFP perception during step descent after induction of increased HIR better reflects the usual functional disturbance associated with PFP.…”
Section: Discussionmentioning
confidence: 92%
“…The overall level of PFP was assessed by a Chinese version of the Kujala scale [21], which is one of the most widely used instruments to quantify the functional disturbance associated with PFP. The Kujala scale consists of 13 multiple choice questions that measure the level of signs and symptoms, and extent of disturbance of functional activities that are related to PFP.…”
Section: Evaluation Of Pfpmentioning
confidence: 99%
“…На сегодняшний день уже опубликовано множество статей, посвященных языковой, культурной адаптации и валидации перевода опросника Kujala на разные языки [15][16][17][18][19]. Широкое применение опросник Kujala получил в группе исследований по поводу рецидивирующей нестабильности надколенника [20].…”
Section: Discussionunclassified